Identifying key factors for optimising performance in Kurash athletes: A focus on biomotor and psychological elements - Irfan, Muhammad; Tomoliyus; Sukamti, Endang Rini; Fitrianto, Ari Tri; Habibie, Muhammad (Journal Sport Area, 2024)
Background Problems: Kurash is a traditional martial art and sport that plays an important role in promoting physical culture and a healthy lifestyle among young people. However, the specific physical and psychological factors that influence performance in Kurash, a martial arts sport, remain unclear. Research Objectives: This study aims to identify the dominant physical and psychological elements affecting Kurash sport performance. Methods: A quantitative, descriptive correlational approach was employed, involving 12 coaches and 40 Kurash athletes from South Kalimantan. Physical indicators were measured using anthropometric data (e.g., height, arm length) and biomotor skills (e.g., muscle strength, flexibility, speed). Aerobic tests assessed physiological capacity, and validated questionnaires evaluated psychological factors such as anxiety, concentration, self-confidence, and motivation. Data analysis was conducted using Partial Least Squares (PLS). Findings and Results: The study's results revealed two main findings. First, the dominant physical factors in kurash sport include arm muscle strength, back and leg muscle strength, flexibility, balance, arm muscle explosiveness, speed, and aerobic capacity. Meanwhile, the main psychological factors are anxiety and self-confidence. Secondly, physiological, biomotor, and psychological aspects were shown to contribute 68.7% to kurash sport performance, while anthropometric data was deemed insufficient to determine the main factors affecting performance. Biomotor, physiological, and psychological variables had a significant influence on kurash sport. Conclusion: The findings demonstrate that biomotor, physiological, and psychological factors substantially affect the performance of Kurash athletes. However, certain constraints, such as the restricted sample size and lack of longitudinal assessment, affected the results. Future research should use larger samples and more comprehensive approaches to investigate the development of physical and psychological elements in Kurash.